Self-lubricating retainer with functional structure, preparation method of self-lubricating retainer and bearing

By designing a self-lubricating cage with a copper ring support layer, combining the material formula of polytetrafluoroethylene and copper powder and the discharge plasma sintering process, the cage is solved, and the cage is broken, poor thermal conductivity and insufficient wear resistance during high-speed operation is achieved, and compatibility of strength, thermal conductivity and wear resistance is improved, and the reliability and life of the bearing is improved.

CN119878708AActive Publication Date: 2025-04-25LUOYANG BEARING RES INST CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411862143.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

When existing solid lubricated bearings operate at high speed, the cage is prone to breaking, poor thermal conductivity, and insufficient wear resistance, resulting in increased bearing temperature, stuck, and even accidents.

Method used

A self-lubricating cage with a functional structure is designed, using a copper ring as the support layer, and the raw materials of the outer and inner functional areas include polytetrafluoroethylene and copper powder, and the strength, thermal conductivity and wear resistance of the cage are improved through discharge plasma sintering and annealing.

Benefits of technology

It achieves multi-parameter compatibility of the strength, thermal conductivity and wear resistance of the cage, reduces the risk of breakage and heat-resistant wear during high-speed operation, and improves the reliability and life of the bearing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119878708A_ABST
    Figure CN119878708A_ABST
Patent Text Reader

Abstract

The invention provides a self-lubricating retainer with a functional structure, a preparation method of the self-lubricating retainer and a bearing. The self-lubricating retainer sequentially comprises an outer functional area, a copper ring and an inner functional area from outside to inside in the radial direction, and raw materials of the outer functional area and the inner functional area comprise polytetrafluoroethylene and copper powder; on any radial cross section of the retainer, the outer functional area and the inner functional area meet any one of the following two conditions: (1) each of the outer functional area and the inner functional area only comprises one layer, and the components of raw materials of the outer functional area and the inner functional area are the same; (2) the outer functional area and the inner functional area both comprise n functional layers combined in the radial direction, n is larger than or equal to 2, components of raw materials of the outer functional area and the inner functional area are symmetrically distributed with the copper ring as the center layer, the content of copper powder is gradually reduced from the center layer to the surface, and the content of polytetrafluoroethylene is gradually increased from the center layer to the surface. The retainer prepared by the invention not only has higher strength, but also has good heat-conducting property and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of bearing manufacturing, in particular to a self-lubricating retainer with a functional structure and a preparation method thereof, and a bearing. Background Art

[0002] Solid lubrication bearings are mainly used in the field of low-speed or intermittent space mechanisms due to their advantages of self-lubrication, long life, no pollution, and radiation resistance. At present, solid lubrication bearings in the aerospace field mostly use cages based on polytetrafluoroethylene. Through the operation of the bearing, the cage material with lubricating properties is transferred to the steel balls and raceways to form a solid lubrication film, achieving friction reduction properties and ensuring the service life of the bearing.

[0003] With the development of space technology, higher requirements are placed on the high-speed performance of solid-lubricated bearings. As the bearing speed increases, the high-speed effect will increase the impact and collision of the steel ball on the cage. When the force on the cage exceeds the yield strength of the polytetrafluoroethylene-based material, the cage will break. Some bearings install two metal reinforcement rings at both ends of the cage, and rivet the cage and the reinforcement rings together to improve the overall strength of the cage. However, the riveting process is complicated, the labor requirements are high, and the qualified rate of finished products is low. In addition, the thermal conductivity of non-metallic cages is poor. For high-speed bearings without a cooling system, the increased heat generation will cause the bearing temperature to rise, which will seriously affect the bearing's operating performance and reliability. At the same time, the high-speed effect will aggravate the friction and wear of the cage pocket, which is easy to cause the accumulation of wear debris, resulting in bearing stagnation and jamming. In severe cases, it will cause the spindle to shut down or even cause an accident.

[0004] Based on this, it is necessary to design a new self-lubricating cage and its preparation method, which can effectively improve its thermal conductivity and wear resistance while improving the strength of the cage. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides a self-lubricating retainer with a functional structure and a preparation method thereof, and a bearing. The retainer prepared by the method of the present invention not only has high strength, but also has good thermal conductivity and wear resistance.

[0006] In order to achieve the above object, the specific scheme adopted by the present invention is:

[0007] On the one hand, the present invention discloses a self-lubricating retainer with a functional structure, wherein the self-lubricating retainer includes an outer functional area, a copper ring, and an inner functional area in sequence from the outer surface to the inner surface along the radial direction, and the raw materials of the outer functional area and the inner functional area include polytetrafluoroethylene and copper powder; on any radial cross section of the retainer, the outer functional area and the inner functional area meet any one of the following two conditions: (1) The outer functional area and the inner functional area each contain only one layer, and the components of the raw materials of the outer functional area and the inner functional area are the same; (2) Both the outer functional zone and the inner functional zone include n functional layers combined in the radial direction, n≥2, and the components of the raw materials of the outer functional zone and the inner functional zone are symmetrically distributed with the copper ring as the central layer, and the content of copper powder gradually decreases from the central layer to the surface, while the content of polytetrafluoroethylene gradually increases from the central layer to the surface.

[0008] Furthermore, in terms of weight percentage, the raw materials of the outer functional area and the inner functional area include 50-80% polytetrafluoroethylene, 10-50% copper powder, and 0-10% polyimide fiber, and the length of the polyimide fiber is 0.1-3 mm.

[0009] On the other hand, the present invention discloses a method for preparing a self-lubricating cage with a functional structure, which mainly comprises the following steps: Step S1: Processing copper ring The copper ring is processed by using a copper rod, and a number of pre-pocket holes are processed at equal intervals on the side wall of the copper ring; Step S2: preparing the mixture 50-80% of polytetrafluoroethylene, 10-50% of copper powder, and 0-10% of polyimide fiber are taken by weight respectively, and the polytetrafluoroethylene is placed in a low temperature environment below 5°C for 12 hours, and then put into a high-speed mixer together with other raw materials for stirring, and the water cooling flow rate of the high-speed mixer is controlled so that the temperature in the high-speed mixer is below 10°C, and mixed evenly to obtain a mixture; If both the outer functional layer and the inner functional area include only one layer, then only one type of mixed material is required; if both the outer functional area and the inner functional area include n functional layers combined in the radial direction, then n types of mixed materials are required; Step S3: preparing finished cage Placing the copper ring in a cylindrical mold, ensuring that the copper ring is in the middle of the mold cavity, and filling the mixed material prepared in step S2 into the mold cavity; placing the mold in a spark plasma sintering furnace, at a temperature of 30°C, at a pressure of 3-10MPa for 3-5min, then rapidly heating to 250-280°C at a heating rate of 60-150°C / min, the sintering pressure is 15-50MPa, the holding time is 2-7min, then heating to 330-360°C at the same heating rate, the sintering pressure is 3-10MPa, the holding time is 3-8min, and finally water cooling is reduced to below 100°C in 3-5min to obtain a blank; annealing the blank at 150-200°C for 2-4h, then scanning the blank with an industrial CT to determine the position of the copper ring and the pre-pocket hole, using a high-speed precision lathe to process the blank to a target size, and processing the pocket hole to obtain a processed body; If the outer functional layer and the inner functional area each contain only one layer, the preparation is completed and the finished retainer is obtained; if the outer functional area and the inner functional area both contain n functional layers combined in the radial direction, the processed body obtained in the previous step is put back into the mold, and different mixtures are filled into the mold, and step S3 (n-1) is repeated for times to obtain the finished retainer.

[0010] Further, in step S1, in step S1, the height of the copper ring = the height of the finished retaining frame - (1~3) mm, the diameter of the pre-pocket hole = the diameter of the finished retaining frame pocket hole + (1~2) mm, and the wall thickness of the copper ring = the wall thickness of the finished retaining frame / (1.5~2); the middle diameter of the copper ring is related to the bearing guiding method, wherein, when the bearing guiding method is external guiding, the middle diameter of the copper ring = the middle diameter of the finished retaining frame + (0.5~1.0) mm; when the bearing guiding method is internal guiding, the middle diameter of the copper ring = the middle diameter of the finished retaining frame - (0.5~1.0) mm.

[0011] Further, in step S3, if the outer functional zone and the inner functional zone both contain n functional layers combined in the radial direction, when processing the Mth layer, 1<M≤n, the diameter of the pocket = the pre-pocket diameter - ((1~2) / n)*M, so that the area around the pocket also has n functional layers in the axial direction.

[0012] Furthermore, in step S3, the mold is prepared by isostatically pressed graphite based on carbon microspheres, the graphite has a flexural strength of 70-100 MPa, a thermal conductivity of 70-100 W / m·K, and a density of 1.75-1.90 g / cm 3 .

[0013] Furthermore, the mold height = 3×the copper ring height, the mold inner diameter = the copper ring outer diameter + (5-8) mm, and the mold outer diameter = (1.5-2)×the mold inner diameter.

[0014] Furthermore, the roughness of the inner and outer surfaces of the copper ring is not less than 45 μm.

[0015] In yet another aspect, the present invention discloses a bearing, including a retaining frame, wherein the retaining frame is the above-mentioned self-lubricating retaining frame with a functional structure.

[0016] Beneficial effects:

[0017] (1) The self-lubricating cage designed in the present invention can achieve compatibility of multiple parameters such as strength, thermal conductivity, wear resistance and lubrication. The copper ring is used as the supporting layer of the cage, which effectively enhances the strength of the cage, improves the thermal conductivity of the cage, and reduces the risk of cage breakage, heat generation and non-wear resistance under high speed conditions.

[0018] (2) The present invention adopts spark plasma sintering. Compared with the traditional cold pressing and sintering of polytetrafluoroethylene, the sintering time is effectively shortened from the traditional 4 to 6 hours to within 20 minutes, avoiding the deformation of the copper ring at high temperature caused by the traditional sintering process. At the same time, combined with annealing treatment, the internal stress is further released to ensure the processing accuracy of the finished retainer.

[0019] (3) The present invention effectively solves the problem of poor adhesion between polytetrafluoroethylene and metal materials by designing formulas and controlling processing technology, and avoids delamination during the processing process. In addition, the present invention realizes the functionalization of the pocket structure by prefabricating the pockets, and at the same time controls the force points between the steel ball and the pockets at the copper ring, solving the problem of the cage not being wear-resistant during high-speed operation.

[0020] (4) The present invention uses carbon microsphere-based fine-grained isostatically pressed graphite as a graphite mold. The graphite mold has high mechanical strength and good thermal conductivity. The large-size retainer produced by sintering is made of uniform material, and there is no problem of the core not being burned through, and the service life is long.

[0021] (5) The present invention adopts high-strength and high-modulus polyimide short fibers to modify polytetrafluoroethylene, which effectively improves the wear resistance of polytetrafluoroethylene. At the same time, unlike the commonly used glass fibers, since polyimide has certain self-lubricating properties, the wear debris can also act as a lubricant when the bearing runs at high speed, and the abrasion of the raceway will not occur. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the CT detection image of the blank in Example 1. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] The present invention provides a self-lubricating cage and a preparation method thereof, and a bearing. The cage has improved strength while effectively improving the thermal conductivity and wear resistance of the material.

[0025] The self-lubricating retainer of the present invention includes an outer functional area, a copper ring, and an inner functional area in sequence from the outer surface to the inner surface along the radial direction, and the raw materials of the outer functional area and the inner functional area include polytetrafluoroethylene and copper powder; on any radial cross section of the retainer, the outer functional area and the inner functional area meet any one of the following two conditions: (1) The outer functional area and the inner functional area each contain only one layer, and the components of the raw materials of the outer functional area and the inner functional area are the same; (2) Both the outer functional zone and the inner functional zone include n functional layers combined in the radial direction, n≥2, and the components of the raw materials of the outer functional zone and the inner functional zone are symmetrically distributed with the copper ring as the central layer, and the content of copper powder gradually decreases from the central layer to the surface, while the content of polytetrafluoroethylene gradually increases from the central layer to the surface.

[0026] Wherein, by weight percentage, the raw materials of the outer functional area and the inner functional area include 50-80% polytetrafluoroethylene, 10-50% copper powder, and 0-10% polyimide fiber, and the length of the polyimide fiber is 0.1-3 mm.

[0027] The preparation method is described in detail below. A preparation method of a self-lubricating cage mainly includes the following steps: Step S1: Processing copper ring A copper ring is processed by using a copper rod, and a number of pre-pocket holes are processed at equal intervals on the side wall of the copper ring; wherein, the height of the copper ring = the height of the finished cage - (1-3) mm, the diameter of the pre-pocket hole = the diameter of the finished cage pocket + (1-2) mm, and the wall thickness of the copper ring = the wall thickness of the finished cage / (1.5-2); the middle diameter of the copper ring is related to the bearing guiding method, wherein, when the bearing guiding method is external guiding, the middle diameter of the copper ring = the middle diameter of the finished cage + (0.5-1.0) mm; when the bearing guiding method is internal guiding, the middle diameter of the copper ring = the middle diameter of the finished cage - (0.5-1.0) mm; Step S2: preparing the mixture 50-80% of polytetrafluoroethylene, 10-50% of copper powder, and 0-10% of polyimide fiber are taken by weight respectively, and the polytetrafluoroethylene is placed in a low temperature environment below 5°C for 12 hours, and then put into a high-speed mixer together with other raw materials for stirring, and the water cooling flow rate of the high-speed mixer is controlled so that the temperature in the high-speed mixer is below 10°C, and mixed evenly to obtain a mixture; If both the outer functional layer and the inner functional area include only one layer, then only one type of mixed material is required; if both the outer functional area and the inner functional area include n functional layers combined in the radial direction, then n types of mixed materials are required; Step S3: preparing finished cage The mold is made of carbon microsphere-based fine-grained isostatic graphite. The graphite has a flexural strength of 70-100 MPa, a thermal conductivity of 70-100 W / m·K, and a density of 1.75-1.90 g / cm 3; Place the copper ring in a barrel-shaped mold, ensure that the copper ring is in the middle of the mold cavity, and fill the mixed material prepared in step S2 into the mold cavity; Place the mold in a spark plasma sintering furnace, at a temperature of 30°C, maintain the pressure at a pressure of 3-10MPa for 3-5min, then quickly heat up to 250-280°C at a heating rate of 60-150°C / min, the sintering pressure is 15-50MPa, and the heat preservation time is 2-7min, then heat up to 330-360°C at the same heating rate, the sintering pressure is 3-10MPa, and the heat preservation time is 3-8min, and finally water cool down to below 100°C in 3-5min to obtain a blank; Anneal the blank at 150-200°C for 2-4h, then use industrial CT to scan the blank to determine the position of the copper ring and the pre-pocket hole, use a high-speed precision lathe to process the blank to the target size, and process the pocket hole to obtain a processed body; If the outer functional layer and the inner functional area each contain only one layer, the preparation is completed and the finished retainer is obtained; if the outer functional area and the inner functional area both contain n functional layers combined in the radial direction, the processed body obtained in the previous step is put back into the mold, and different mixtures are filled into the mold, and step S3 (n-1) is repeated for times to obtain the finished retainer.

[0028] Among them, the mold height = 3×copper ring height, the mold inner diameter = copper ring outer diameter + (5~8) mm, and the mold outer diameter = (1.5~2)×mold inner diameter.

[0029] In step S3, in step S3, if the outer functional area and the inner functional area both contain n functional layers combined in the radial direction, when processing the Mth layer, 1<M≤n, the diameter of the pocket = pre-pocket diameter-((1~2) / n)*M, so that the area around the pocket also has n functional layers in the axial direction, and the nth circle is closest to the center of the pocket, and the first circle is farthest from the center of the pocket.

[0030] Example 1

[0031] The inner diameter of the cage is set to d = 29.0 mm, the outer diameter is D = 35.0 mm, the height is H = 11.0 mm, and the pocket diameter Db is = 7.5 mm. Under the above parameter settings, the five steps of the present invention are described as follows: S1. Processing of copper rings The copper rod is roughly processed into a copper ring, the copper ring height = the finished cage height - 1 = 10.0mm, the pre-pocket holes are processed at equal intervals, the pre-pocket hole diameter = the finished cage pocket hole diameter + 1 = 8.5mm, the copper ring wall thickness = the finished cage wall thickness / 1.5 = ((35.0-29.0) / 2) / 1.5 = 2mm, the copper ring outer diameter = 33.5mm, and a large cutting edge tool is used during processing to make the copper ring surface rougher to improve the bonding strength between different materials and avoid delamination; S2. Preparation of mixed materials Take 50% polytetrafluoroethylene and 50% copper powder by weight respectively, place the polytetrafluoroethylene in a low temperature environment below 5°C for 12 hours in advance, then put them into a high-speed mixer for stirring, control the water cooling flow rate of the high-speed mixer so that the temperature in the high-speed mixer is below 10°C, and mix to prepare a mixture; S3. Mould composition The mold is made of carbon microsphere-based fine-grained isostatically pressed graphite, the graphite has a flexural strength of 70 MPa, a thermal conductivity of 100 W / m·K, and a density of 1.75 g / cm 3 . Mold height = 3 × copper ring height = 30.0 mm, mold inner diameter = copper ring outer diameter + 5 = 38.5 mm, mold outer diameter = 2 × mold inner diameter = 77.0 mm; S4, spark plasma sintering After placing the copper ring in the middle of the mold, ensure that the copper ring is in the middle of the mold cavity, fill the mixed material prepared in step S2 into the mold cavity, so that both sides of the copper ring and the pre-pocket hole are filled with the mixed material; then, at 30°C and 3MPa, maintain the pressure for 4 minutes, quickly heat up to 280°C at 150°C / min, sinter at 15MPa, and keep warm for 2 minutes, heat up to 350°C at the same heating rate, sinter at 3MPa, and keep warm for 3 minutes, then water cool down to below 100°C in 3 minutes to obtain a green body; S5, precision machining cage The blank was annealed at 150 °C for 3 h, and then the blank was scanned using industrial CT to determine the position and size of the copper ring, especially the position of the pre-pocket hole, such as Figure 1 As shown, the white part is a copper ring and the gray part is a mixed material. A high-speed precision lathe is used to process the blank (including size processing and pocket hole processing). The processing speed is controlled during the process to ensure the processing accuracy while further avoiding defects such as delamination and curling to obtain the final product.

[0032] Example 2

[0033] The inner diameter of the cage is set to d=68.5 mm, the outer diameter is set to D=78.5 mm, the height is set to H=17.0 mm, and the pocket diameter Db is set to =11.5 mm. Under the above parameter settings, the steps of the present invention are described as follows: S1. Processing of copper rings The copper rod is roughly processed into a copper ring, the copper ring height = the finished cage height - 3 = 14.0 mm, the pre-pocket hole diameter = the finished cage pocket hole diameter + 1 = 12.5 mm, the copper ring wall thickness = the finished cage wall thickness / 2 = ((78.5-68.5) / 2) / 2 = 2.5 mm, the copper ring outer diameter = 74.0 mm, and a large cutting edge tool is used during processing to make the copper ring surface rougher to improve the bonding strength between different materials and avoid delamination; S2. Preparation of mixed materials 60% polytetrafluoroethylene and 40% copper powder are taken by weight, the polytetrafluoroethylene is placed in a low temperature environment below 5°C for 12 hours in advance, and then put into a high-speed mixer together for stirring, and the water cooling flow rate of the high-speed mixer is controlled so that the temperature in the high-speed mixer is below 10°C, and the first mixture is prepared by mixing; 80% polytetrafluoroethylene, 10% copper powder, and 10% polyimide fiber are taken by weight, the polytetrafluoroethylene is placed in a low temperature environment below 5°C for 12 hours in advance, and then put into a high-speed mixer together for stirring, and the water cooling flow rate of the high-speed mixer is controlled so that the temperature in the high-speed mixer is below 10°C, and the second mixture is prepared by mixing; wherein the length of the polyimide short fiber is 0.1mm; S3. Mould composition The mold is made of carbon microsphere-based fine-grained isostatically pressed graphite, the graphite has a flexural strength of 80 MPa, a thermal conductivity of 80 W / m·K, and a density of 1.85 g / cm 3 ; Mold height = 3 × copper ring height = 42.0 mm, mold inner diameter = copper ring outer diameter + 8 = 82.0 mm, mold outer diameter = 1.5 × mold inner diameter = 123.0 mm; S4, one-shot spark plasma sintering After placing the copper ring in the middle of the mold, ensure that the copper ring is in the middle of the mold cavity, fill the first mixed material prepared in step S2 into the mold cavity, so that both sides of the copper ring and the pre-pocket hole are filled with the first mixed material; then, at 30°C and 10MPa, maintain the pressure for 5min, quickly heat to 260°C at 110°C / min, pressure is 38MPa, and keep the temperature for 6min, heat to 360°C at the same heating rate, pressure is 10MPa, and keep the temperature for 5min, then water cool to below 100°C in 4min to obtain the first green body; S5. Precision machining of the first blank The blank was annealed at 180° C. for 4 h, and then the first blank was scanned by industrial CT to determine the position and size of the copper ring, especially the position of the pre-pocket hole, and then the first blank was processed by a high-speed precision lathe (including size processing and pocket hole processing) to obtain a first processed body, wherein the first processed body had an outer diameter of 76.0 mm, an inner diameter of 67.0 mm, a height of 16.0 mm, and a pocket hole diameter of 12 mm; S6, secondary spark plasma sintering The first processed body is placed in the mold to ensure that the first processed body is in the middle of the mold cavity, and the second mixed material prepared in step S2 is filled into the mold cavity so that both sides and the pockets of the first processed body are filled with the second mixed material; then, the pressure is maintained at 30°C and 10MPa for 5 minutes, and the temperature is rapidly increased to 260°C at 110°C / min, the pressure is 38MPa, and the temperature is maintained for 6 minutes, and the temperature is increased to 360°C at the same heating rate, the pressure is 10MPa, and the temperature is maintained for 5 minutes, and then water-cooled to below 100°C in 4 minutes to obtain a second green body; S7. Precision machining of the second blank The second blank is annealed at 180°C for 4 hours, and then the second blank is scanned using industrial CT to determine the position and size of the copper ring, especially the position of the pre-pocket hole. A high-speed precision lathe is then used to process the second blank (including size processing and pocket hole processing). During the process, the processing speed is controlled to ensure the processing accuracy while further avoiding defects such as delamination and curling to obtain the final product.

[0034] Example 3

[0035] The inner diameter of the cage is set to d = 45.0 mm, the outer diameter is D = 51.5 mm, the height is H = 15.0 mm, and the pocket diameter Db is = 10.0 mm. Under the above parameter settings, the five steps of the present invention are described as follows: S1. Processing of copper rings The copper rod is roughly processed into a copper ring, the copper ring height = the finished cage height - 2 = 13.0 mm, the pre-pocket hole diameter = the finished cage pocket hole diameter + 2 = 12.0 mm, the copper ring wall thickness = the finished cage wall thickness / 1.8 = (51.5-45.0) / 2 / 1.8 = 1.8 mm, the copper ring outer diameter = 49.5 mm, and a large cutting edge tool is used during processing to make the copper ring surface rougher to improve the bonding strength between different materials and avoid delamination; S2. Preparation of mixed materials Take 60% polytetrafluoroethylene, 35% copper powder, and 5% polyimide short fibers by weight respectively, place the polytetrafluoroethylene in a low temperature environment below 5°C for 12 hours in advance, and then put them together in a high-speed mixer for stirring, control the water cooling flow rate of the high-speed mixer so that the temperature in the high-speed mixer is below 10°C, and mix to prepare a mixture, wherein the length of the polyimide short fibers is 3mm; S3. Mould composition The mold is made of carbon microsphere-based fine-grained isostatically pressed graphite, the graphite has a flexural strength of 100 MPa, a thermal conductivity of 70 W / m·K, and a density of 1.75 g / cm 3. Mold height = 3 × copper ring height = 39.0mm, mold inner diameter = copper ring outer diameter + 6 = 55.5mm, mold outer diameter = 1.6 × mold inner diameter = 88.8mm; S4, spark plasma sintering After placing the copper ring in the middle of the mold, ensure that the copper ring is in the middle of the mold cavity, and fill the mixed material prepared in step S2 into the mold cavity; then, at 30°C and 4MPa, maintain the pressure for 3min, quickly heat up to 250°C at 60°C / min, the pressure is 50MPa, and the temperature is kept for 7min, and at the same heating rate, the temperature is increased to 330°C, the pressure is 4MPa, and the temperature is kept for 10min, and then water-cooled to below 100°C in 5min to obtain a green body; S5, precision machining cage The blank is annealed at 200°C for 3 hours, and then the industrial CT is used to scan the blank to determine the position and size of the copper ring, especially the position of the pre-pocket hole. A high-speed precision lathe is then used to process the blank (including size processing and pocket hole processing). The processing speed is controlled during the process to ensure the processing accuracy while further avoiding defects such as delamination and curling to obtain the final product.

[0036] Comparative Example 1

[0037] Comparative Example 1 is a traditional polytetrafluoroethylene composite cage, ZYS-PTFE02, that is, a glass fiber modified polytetrafluoroethylene composite cage.

[0038] The tensile strength and wear properties of the retaining frames prepared in Examples 1-3 and the comparative example are tested below. The results are shown in Table 1.

[0039] Table 1 Performance of the cages prepared in Examples 1-3 and Comparative Examples

[0040] From the above table, it can be analyzed that the mechanical properties of the self-lubricating cage prepared by the present invention are significantly improved, and there is no delamination at the fracture of the stretched sample, and the interface bonding force is good. The self-lubricating cage prepared by the present invention has excellent friction and wear properties.

[0041] The bearing using this self-lubricating cage has excellent running-in performance at a high speed of 6000rpm, without any abnormal performance such as noise or howling. After disassembling the bearing, the ring groove transfer film is in good condition.

[0042] The self-lubricating cage can be widely used in space solid-lubricating bearings with higher speed and longer life requirements, meeting the future development needs of space solid-lubricating bearings in my country's aerospace field, with significant economic and social benefits.

[0043] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-lubricating cage with a functional structure, characterized in that: The self-lubricating retainer includes an outer functional area, a copper ring, and an inner functional area in sequence from the outer surface to the inner surface in the radial direction. The raw materials of the outer functional area and the inner functional area include polytetrafluoroethylene and copper powder. On any radial cross section of the retainer, the outer functional area and the inner functional area meet any one of the following two conditions: (1) The outer functional area and the inner functional area each contain only one layer, and the components of the raw materials of the outer functional area and the inner functional area are the same; (2) Both the outer functional zone and the inner functional zone include n functional layers combined in the radial direction, n ≥ 2, and the components of the raw materials of the outer functional zone and the inner functional zone are symmetrically distributed with the copper ring as the central layer, and the content of copper powder gradually decreases from the central layer to the surface, while the content of polytetrafluoroethylene gradually increases from the central layer to the surface.

2. A self-lubricating retainer with a functional structure according to claim 1, characterized in that: In terms of weight percentage, the raw materials of the outer functional area and the inner functional area include 50-80% polytetrafluoroethylene, 10-50% copper powder, and 0-10% polyimide fiber, and the length of the polyimide fiber is 0.1-3 mm.

3. A method for preparing a self-lubricating cage with a functional structure, characterized in that: The main steps are as follows: Step S1: Processing copper ring The copper ring is processed by using a copper rod, and a number of pre-pocket holes are processed at equal intervals on the side wall of the copper ring; Step S2: preparing the mixture Take 50-80% polytetrafluoroethylene, 10-50% copper powder, and 0-10% polyimide fiber by weight, place the polytetrafluoroethylene in a low temperature environment below 5°C for 12 hours, and then put it into a high-speed mixer together with other raw materials for stirring, control the water cooling flow rate of the high-speed mixer so that the temperature in the high-speed mixer is below 10°C, and mix them evenly to obtain a mixture; If both the outer functional layer and the inner functional area include only one layer, then only one type of mixed material is required; if both the outer functional area and the inner functional area include n functional layers combined in the radial direction, then n types of mixed materials are required; Step S3: preparing finished cage Place the copper ring in a barrel-shaped mold to ensure that the copper ring is in the middle of the mold cavity, and fill the mixed material prepared in step S2 into the mold cavity so that both sides of the copper ring and the pre-pocket hole are filled with the mixed material; place the mold in a spark plasma sintering furnace, at a temperature of 30°C, at a pressure of 3-10MPa for 3-5min, then quickly heat to 250-280°C at a heating rate of 60-150°C / min, the sintering pressure is 15-50MPa, and the holding time is 2 ~7min, then heat to 330~360℃ at the same heating rate, sintering pressure is 3~10MPa, holding time is 3~8min, and finally water-cooling is reduced to below 100℃ for 3~5min to obtain a green body; anneal the green body at 150~200℃ for 2~4h, then use industrial CT to scan the green body to determine the position of the copper ring and the pre-pocket hole, use a high-speed precision lathe to process the green body to the target size, and process the pocket hole to obtain a processed body; If both the outer functional layer and the inner functional area contain only one layer, the preparation is completed and the finished retainer is obtained; if both the outer functional area and the inner functional area contain n functional layers combined in the radial direction, the processed body obtained in the previous step is put back into the mold, and different mixtures are filled into the mold. Step S3 (n-1) is repeated for times to obtain the finished retainer.

4. The method for preparing a self-lubricating retainer with a functional structure according to claim 3, characterized in that: In step S1, the height of the copper ring = the height of the finished cage - (1~3) mm, the diameter of the pre-pocket hole = the diameter of the finished cage pocket hole + (1~2) mm, and the wall thickness of the copper ring = the wall thickness of the finished cage / (1.5~2); the copper ring middle diameter size is related to the bearing guiding method, wherein, when the bearing guiding method is external guiding, the copper ring middle diameter = the finished cage middle diameter + (0.5~1.0) mm; when the bearing guiding method is internal guiding, the copper ring middle diameter = the finished cage middle diameter - (0.5~1.0) mm.

5. The method for preparing a self-lubricating retainer with a functional structure according to claim 4, characterized in that: In step S3, in step S3, if the outer functional area and the inner functional area both contain n functional layers combined in the radial direction, when processing the Mth layer, 1<M≤n, the diameter of the pocket = the pre-pocket diameter-((1~2) / n)*M, so that the area around the pocket also has n functional layers in the axial direction.

6. The method for preparing a self-lubricating cage with a functional structure according to claim 3, characterized in that: In step S3, the mold is prepared by isostatically pressed graphite based on carbon microspheres, the graphite has a flexural strength of 70-100 MPa, a thermal conductivity of 70-100 W / m·K, and a density of 1.75-1.90 g / cm 3 .

7. The method for preparing a self-lubricating retainer with a functional structure according to claim 3, characterized in that: Mold height = 3 × copper ring height, mold inner diameter = copper ring outer diameter + (5~8) mm, mold outer diameter = (1.5~2) × mold inner diameter.

8. The method for preparing a self-lubricating retainer with a functional structure according to claim 3, characterized in that: The roughness of the inner and outer surfaces of the copper ring is not less than 45μm.

9. A bearing, including a cage, characterized in that: The retainer is a self-lubricating retainer with a functional structure as described in any one of claims 1 to 2.

Citation Information

Patent Citations

  • Self-lubricating slide bearing by oil lubrication or grease lubrication

    CN101413544A

  • Vibration-damping wear-resistant self-lubricating spindle sleeve and preparation method thereof

    CN106079771A

  • Composite self-lubricating plate and preparation method thereof

    CN110861367A

  • Copper-based graphite self-lubricating gradient functional material and preparation method thereof

    CN111906301A

  • Non-noise composite bearing cage

    CN2427667Y